The Co-Occurrence of Autism and Attention Deficit Hyperactivity Disorder in Children – What Do We Know? - Leitner, Yael (Frontiers in Human Neuroscience, 2014)
Symptoms of Attention Deficit Hyperactivity Disorder (ADHD) and Autistic Spectrum Disorder (ASD) often co-occur. The DSM IV had specified that an ASD diagnosis is an exclusion criterion for ADHD, thereby limiting research of this common clinical co-occurrence. As neurodevelopmental disorders, both ASD and ADHD share some phenotypic similarities, but are characterized by distinct diagnostic criteria. The present review will examine the frequency and implications of this clinical co-occurrence in children, with an emphasis on the available data regarding preschool age. The review will highlight possible etiologies explaining it, and suggest future research directions necessary to enhance our understanding of both etiology and therapeutic interventions, in light of the new DSM V criteria , allowing for a dual diagnosis.